Digital Surveillance and Digitally-disadvantaged Language Communities - Zaugg, Isabelle (My University, 2019)
The issue of digital surveillance often falls outside urgent discussions regarding the need to build digital supports for under- resourced languages. While the benefits of these supports for digitally-disadvantaged language communities are clear, the reality is that standardized script use, standardized spelling, and NLP systems in particular increase a language community’s legibility for digital surveillance. As we build digital supports for Indigenous and minority language communities, we must consider how these tools might be used against them through digital surveillance, and how to combat these risks.
Keywords: digital surveillance; Indigenous communities; language diversity